Exosomal Long Noncoding RNAs Serve as Biomarkers for Liver Disease - Yang, Zixuan; Tang, Naping; Zheng, Minhui; Chang, Yan (Turkish Journal of Gastroenterology, 2023)
Exosomes are tiny vesicles secreted by cells, with a diameter of 40-160 nm, which contain proteins, DNA, mRNA, long noncoding RNA, etc. Because of the low sensitivity and specificity of the conventional biomarkers for liver diseases, it is of utmost importance to discover novel, sensitive, specific, and non-invasive biomarkers. Exosomal long noncoding RNAs have been considered as potential diagnostic, prognostic, or predictive biomarkers in a wide range of liver pathologies. In this review, we discuss the recent progress on exosomal long noncoding RNAs that serve as potential diagnostic, prognostic, or predictive markers and molecular targets in patients with hepatocellular carcinoma, cholestatic liver injury, viral hepatitis, and alcohol-related liver diseases. Cite this article as: Yang Z, Tang N, Zheng M, Chang Y. Exosomal long noncoding RNAs serve as biomarkers for liver disease. Turk J Gastroenterol. 2023;34(7):674-680.